Propolis: anti-Staphylococcus aureus activity and synergism with antimicrobial drugs - Fernandes Jr., Ary [UNESP]; Balestrin, Elaine Cristina [UNESP]; Betoni, Joyce Elaine Cristina [UNESP]; De Oliveira Orsi, Ricardo [UNESP]; De Souza Da Cunha, Maria de Lourdes Ribeiro [UNESP]; Montelli, Augusto Cezar [UNESP] (FapUNIFESP (SciELO), 2005)
Propolis is a natural resinous substance collected by bees from tree exudates and secretions. Its antimicrobial activity has been investigated and inhibitory action on Staphylococcus aureus growth was evaluated The in vitro synergism between ethanolic extract of propolis (EEP) and antimicrobial drugs by two susceptibility tests (Kirby and Bauer and E-Test) on 25 S. aureus strains was evaluated Petri dishes with sub-inhibitory concentrations of EEP were incubated with 13 drugs using Kirby and Bauer method and synergism between EEP and five drugs [choramphenicol (CLO), gentamicin (GEN), netilmicin (NET), tetracycline (TET), and vancomycin (VAN)] was observed. Nine drugs were assayed by the E-test method and five of them exhibited a synergism [CLO, GEN, NET, TET, and clindamycin (CLI)]. The results demonstrated the synergism between EEP and antimicrobial drugs, especially those agents that interfere on bacterial protein synthesis.
Keywords: Antimicrobial drugs; E-test method; Kirby and Bauer method; Propolis; Staphylococcus aureus; antiinfective agent; propolis; drug effect; drug potentiation; human; microbiological examination; newborn; Anti-Bacterial Agents; Drug Synergism; Humans; Infant, Newborn; Microbial Sensitivity Tests; Apoidea; Bacteria (microorganisms)